2003
DOI: 10.1002/jcp.10356
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of membrane‐associated prostaglandin E2 synthase to bone resorption

Abstract: This study initially confirmed that, among prostaglandins (PGs) produced in bone, only PGE(2) has the potency to stimulate osteoclastogenesis and bone resorption in the mouse coculture system of osteoblasts and bone marrow cells. For the PGE(2) biosynthesis two isoforms of the terminal and specific enzymes, membrane-associated PGE(2) synthase (mPGES) and cytosolic PGES (cPGES) have recently been identified. In cultured mouse primary osteoblasts, both mPGES and cyclooxygenase-2 were induced by the bone resorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
28
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 59 publications
4
28
1
Order By: Relevance
“…7). These observations are compatible with our recent finding that mPGES-1 is induced by and mediates the effects of bone-resorptive stimuli in vitro (51). Because mPGES-1 deficiency leads to only 50% reduction of PGE 2 level in the arthritic tissue (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…7). These observations are compatible with our recent finding that mPGES-1 is induced by and mediates the effects of bone-resorptive stimuli in vitro (51). Because mPGES-1 deficiency leads to only 50% reduction of PGE 2 level in the arthritic tissue (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, PGE 2 production was diminished in gingival fibroblasts derived from mPGES-1 knockout mice, compared with wild-type fibroblasts. These results suggest that fibroblasts and smooth muscle cells are important sources of mPGES-1, which may contribute to increased PGE 2 Periodontitis is a chronic inflammatory disease involving interactions among bacterial products, host cells, and inflammatory mediators. The inflammatory response results in destruction of the tissue and alveolar bone supporting the teeth and can ultimately lead to tooth loss.…”
mentioning
confidence: 86%
“…Levels of PGE 2 are elevated in the gingival tissue and gingival fluid of patients with periodontitis, compared with periodontally healthy subjects. [2][3][4][5] It has also been reported that the inhibition of PGE 2 using selective or nonselective nonsteroidal anti-inflammatory drugs decreases periodontal disease progression and reduces alveolar bone resorption, which highlights the significance of PGE 2 in the pathogenesis of periodontal disease. 6 -8 In addition to these findings, bone resorption in lipopolysaccharide-treated mice has been shown to be dependent on PGE 2 synthesis, a finding that might be explained by the observation that PGE 2 stimulates the formation of osteoclasts.…”
mentioning
confidence: 96%
See 2 more Smart Citations